IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM RANGKA PEMERATAAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN BUNGO - Deni Handani, Mela Sari, Ira Devi Lia (Dialektika Publik, 2019)
ABSTRACT Policy of Assistance to the Family Hope Program (PKH) through Law Number 40 of 2004 concerning the National Social Security System which was followed up with Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning PKH. One way that has been done by the government to prosper and reduce poverty by giving assistance to shortage society. The aim of this study was to identify the Implementation of the Family Hope Program in the framework of the distribution of community welfare in Bungo District. The study used descriptive method with qualitative. Data analysis using data collection, data reduction, presentation and drawing conclusions and verification. The results showed that the implementation of the policies carried out by related government agencies was improving the quality of life in the fields of education and health, but the reality in the field was found that the implementation of the family of hope program in Bungo district had not been able to fully realize equitable welfare for the community, this was indicated from the distribution of funds that had not been equitable and injustice in determining the participants receiving PKH funds. Keywords: Implementation, Family Hope Program (PKH), Community Welfare.